Objektivikasi Islam dalam Tema-Tema Pekerjaan Sosial (Konkretisasi Nilai-nilai Islam dalam Praktik Pekerjaan Sosial) - -, Noorkamilah (Social Welfare Study Program, 2017)
The metamorphosis of Islamic Education Institution such as IAIN into UIN has brought consequences, i. e. objectification of social sciences to Islamic value. This includes themes in social work discipline; as a science or as a profession. This article argues that prophetic institutionalization is crucial and significant in adjusting with challenges regarding not only as academic but also as practical purposes. Through a qualitative approach, several Islamic basic principles found that may serve as a guiding principle of general and specific themes in social work science, among general aspects are rahmatan lil ‘alamin, al-‘Amal al-Shalih, al-Ikhlas, empowerment of vurnerable group (mustadh’afin), while the specific consists of ta’awwun, tawashshou, amr ma’ruf nahi munkar, sadaqa, covering one’s ‘aib and tawakkal. Keywords: Objectivation, Islam and Social Work